Kajian Literatur Faktor yang Berhubungan dengan Kesehatan Mental Pada Remaja - Fatya Ulya; Noor Alis Setiyadi (Nur Science Institute, 2021)
Background: Adolescents are a transitional period between childhood and adulthood and formulate their identity as adults, where adolescents experience changes that occur in their bodies, dev elop new thoughts and are easily aroused erotically so that they affect adolescent mental health. Purpose: to conduct a literature review from various journals to explain the factors associated with mental health in adolescents. The method used is literature review using two databases, namely Google Scholar and Pubmed using the keywords